Poly(brilliant green) and poly(thionine) modified carbon nanotube coated carbon film electrodes for glucose and uric acid biosensors - Ghica, M. Emilia (2014)
Poly(brilliant green) (PBG) and poly(thionine) (PTH) films have been formed on carbon film electrodes (CFEs) modified with carbon nanotubes (CNT) by electropolymerisation using potential cycling. Voltammetric and electrochemical impedance characterisation were performed. Glucose oxidase and uricase, as model enzymes, were immobilised on top of PBG/CNT/CFE and PTH/CNT/CFE for glucose and uric acid (UA) biosensing. Amperometric determination of glucose and UA was carried out in phosphate buffer pH 7.0 at −0.20 and +0.30 V vs. SCE, respectively, and the results were compared with other similarly modified electrodes existing in the literature. An interference study and recovery measurements in natural samples were successfully performed, indicating these architectures to be good and promising biosensor platforms.